Epistemologi Pendidikan Agama Islam Alam Melayu: Transformasi Lembaga Keilmuan di Sumatera Barat dan Sumatera Utara - Miswari, Miswari (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2024)
This article aims to review the history of the development of Islamic religious education in the Malay World, especially West Sumatra and North Sumatra. This qualitative research uses a descriptive analytical approach. Data is collected from various library sources, then analyzed, verified and presented narratively. The results of the research show that West Sumatra is not only the heart of the renewal of Islamic religious education in the Malay World, but also a source of energy for the renewal of Islamic thought in Indonesia. The renewal of Islamic religious education in West Sumatra influenced thinking about Islamic religious education in other regions, including North Sumatra. The most massive renewal of Islamic religious education in North Sumatra occurred in the modern Islamic boarding school education curriculum.